Exploring the intersection of education policy and discourse analysis: An introduction - Jessica Nina Lester; Chad R. Lochmiller; Rachael Gabriel (Arizona State University, 2017)
In this article, we introduce the special issue focused on diverse perspectives to discourse analysis for education policy. This article lays the foundation for the special issue by introducing the notion of a third generation of policy research - a strand of policy research we argue is produced at the intersection of education policy and discourse analysis. We also very briefly discuss discourse analysis writ large, noting that there is no single definition or orientation. Then, we present the six articles included in the special issue, highlighting the ways in which they offer contemporary understandings of the varying applications of discourse analytic perspectives to the study of education policy. We conclude by discussing key policy and methodological implications, as well as future directions for policy scholars working at the intersection of education policy and discourse analysis.